Development of white bread fortified with calcium derived from eggshell powder - Tuan Zainazor Tuan Chilek; Nur Ayuni Kairuaman; Fisal Ahmad; Rahijan Abdul Wahab; Amir Izzwan Zamri; Azizah Mahmood (Penerbit Universiti Kebangsaan Malaysia, 2018)
Bread is commonly used mostly around the world which obtained from grains, legumes, tubers and other fortified ingredients. Eggshell makes up from 9-12% of the total egg weight that consists largely of calcium carbonate (94%) with some magnesium carbonate and calcium phosphate deposited in the organic matrix. The objectives of this study were to produce white bread fortified with calcium derived from the eggshell powder and to study the physicochemical changes, microbiological status and sensory evaluation of the product. The main analyses were done on specific volume, texture, colour, proximate analysis, calcium determination by ICP-MS and microbiological test for the determination of shelf life. Besides, acceptance test was also carried out. The result showed that increasing of the eggshell did not have any effect on the specific volume, springiness, cohesiveness and colour but affect the hardness of the bread. Furthermore, addition of the eggshell significantly increased (p<0.05) the moisture content, ash, fibre but decreased the carbohydrate. However, there were no significantly different between sample in terms of fat and protein. The bread with addition of eggshell have potential to be produced and accepted by the consumer especially the bread with fortification of 2% egg shell powder.